Ferromagnetism and matrix-dependent charge transfer in strained LaMnO3-LaCoO3 superlattices - Wu, Liang (2019)
Interfacial magnetism at transition-metal oxide interfaces is of tremendous interest. The emergence of ferromagnetism and a matrix-dependent charge transfer between Co and Mn ions in the interdiffusion region of compressively strained LaMnO3–LaCoO3 superlattices (SLs) were studied. The SLs exhibit considerable ferromagnetism, which is negligible in both constituents. This is explained by the matrix-dependent charge transfer between Co and Mn ions. That is, the valence state of diffused Co ions into LaMnO3 shifts from 3+ to 2+ by adopting one electron from Mn3+, inducing the same amount of Mn4+, while the Mn ions that diffuses into LaCoO3 remains Mn3+.